Correlation Between Thyroid Hormone and Controlled Attenuation Parameters: A Cross-Sectional Population-Based Study - Li S; Wu X; Yu J; Jiang J; Qi R; Chen B; Li Z (Diabetes, Metabolic Syndrome and Obesity)
Sumei Li,1,* Xingye Wu,2,* Jingming Yu,2 Jiaqin Jiang,2 Ruibing Qi,2 Bing Chen,3 Zhengming Li2 1Department of Endocrinology and Metabolism, Guangxi Hospital Division of The First Affiliated Hospital, Sun Yat-sen University, Nanning, 530022, People’s Republic of China; 2Department of Endocrinology and Metabolism, Guangxi Academy of Medical Sciences and the People’s Hospital of Guangxi Zhuang Autonomous Region, Nanning, 530021, People’s Republic of China; 3Department of Endocrinology, Wuming Hospital of Guangxi Medical University, Nanning, 530199, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhengming Li, Email zmli@gxams.org.cnObjective: The aim of the present study was to investigate how thyroid hormone levels are related to controlled attenuation parameters (CAP), which may provide insights for understanding the role of these factors in hepatic steatosis.Methods: A total of 3461 participants who underwent CAP diagnosis between 2018 and 2023 were included. The associations between thyroid hormone levels and CAP were evaluated through multiple linear regression, restricted cubic splines (RCS) and threshold effect analyses.Results: Multiple linear regression analysis revealed an inverse relationship between free thyroxine (FT4) and CAP, with a coefficient of − 0.855 and a confidence interval of − 1.297 to − 0.412. The negative connection in a subset examination persisted in males [− 0.729 (− 1.295, − 0.162)] and females [− 1.234 (− 1.996, − 0.473)]. A strong correlation was found between free 3,5,3′-triiodothyronine (FT3) and CAP, with values of 2.182 (1.154, 3.211). Further analysis was conducted on both male [1.626 (0.188, 3.065)] and female [2.835 (1.137, 4.533)] subgroups. In the severe liver steatosis group, there was a significant negative correlation between FT3 and CAP based on the subgroup analysis stratified by the level of liver steatosis [− 3.804 (− 6.711, − 0.898)]. The RCS analysis showed a nonlinear association between FT4 and CAP, with a turning point at 11.14 pmol/L.Conclusion: There was a significant linear and nonlinear relationship between FT4, FT3 and CAP. Thyroid hormones could have a significant impact on liver steatosis, offering fresh perspectives on how to prevent and treat this condition.Keywords: thyroid hormone, nonalcoholic fatty liver disease, free thyroxine, free 3,5,3′-triiodothyronine, controlled attenuation parameters, transient elastography